Gestión documental y su incidencia en la reducción de quejas y reclamos en la Unidad Ejecutora Salud Ucayali Contamana 2025 - Melgar Navarro, Luis Miguel (2025)
The final report's main objective was to determine the impact of document management on the reduction of complaints and claims in the Ucayali Contamana 2025 Health Executive Unit. It used a basic approach, a descriptive-correlational level, and a non-experimental design. The study included a population of 103 administrative staff members, who were used to collect information and data. The results showed that document management was rated as average (26%), since an orderly structure was only occasionally maintained to organize documents. Copying and duplication procedures were carried out relatively efficiently, and documents were occasionally sent quickly to the appropriate areas. However, the description of documents was rarely complete, and compliance was only occasionally verified before filing. Regarding the variable "reduction of complaints and claims," 26% of participants considered it to be average, since the complaints service was sometimes available during all working hours. However, the areas involved never collaborated with each other to resolve complaints efficiently; and responses to complaints were never communicated in clear and understandable language. Finally, document management presents the highest positive correlation (R=0.813) and explains 66.0% of the variability; it is followed by management and processing (R=0.740; 54.8%), file organization (R=0.661; 43.7%), document transfer (R=0.615; 37.8%), long term preservation (R=0.604; 36.4%), and planning, with a moderate effect (R=0.599; 35.9%); production also has a significant impact (R=0.548; 30.0%), while final disposition (R=0.462; 21.3%) and appraisal (R=0.384; 14.8%) contribute smaller but relevant effects.